Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find [tex]\( f(3) \)[/tex] and [tex]\( g(-4) \)[/tex] using the given functions [tex]\( f(x) = -4x + 4 \)[/tex] and [tex]\( g(x) = -2x^3 - 3 \)[/tex], follow the steps below for each function.
### Step-by-Step Solution
1. Calculate [tex]\( f(3) \)[/tex]:
The function [tex]\( f(x) = -4x + 4 \)[/tex].
Substitute [tex]\( x = 3 \)[/tex] into the function:
[tex]\[ f(3) = -4(3) + 4 \][/tex]
Simplify the expression inside the parentheses first:
[tex]\[ f(3) = -12 + 4 \][/tex]
Finally, combine the terms:
[tex]\[ f(3) = -8 \][/tex]
So, [tex]\( f(3) = -8 \)[/tex].
2. Calculate [tex]\( g(-4) \)[/tex]:
The function [tex]\( g(x) = -2x^3 - 3 \)[/tex].
Substitute [tex]\( x = -4 \)[/tex] into the function:
[tex]\[ g(-4) = -2(-4)^3 - 3 \][/tex]
Calculate the cube of [tex]\(-4\)[/tex]:
[tex]\[ (-4)^3 = -64 \][/tex]
Substitute [tex]\( -64 \)[/tex] back into the function:
[tex]\[ g(-4) = -2(-64) - 3 \][/tex]
Multiply the constants:
[tex]\[ -2 \cdot -64 = 128 \][/tex]
Finally, combine the terms:
[tex]\[ g(-4) = 128 - 3 \][/tex]
[tex]\[ g(-4) = 125 \][/tex]
So, [tex]\( g(-4) = 125 \)[/tex].
### Final Answers
[tex]\[ f(3) = -8 \][/tex]
[tex]\[ g(-4) = 125 \][/tex]
### Step-by-Step Solution
1. Calculate [tex]\( f(3) \)[/tex]:
The function [tex]\( f(x) = -4x + 4 \)[/tex].
Substitute [tex]\( x = 3 \)[/tex] into the function:
[tex]\[ f(3) = -4(3) + 4 \][/tex]
Simplify the expression inside the parentheses first:
[tex]\[ f(3) = -12 + 4 \][/tex]
Finally, combine the terms:
[tex]\[ f(3) = -8 \][/tex]
So, [tex]\( f(3) = -8 \)[/tex].
2. Calculate [tex]\( g(-4) \)[/tex]:
The function [tex]\( g(x) = -2x^3 - 3 \)[/tex].
Substitute [tex]\( x = -4 \)[/tex] into the function:
[tex]\[ g(-4) = -2(-4)^3 - 3 \][/tex]
Calculate the cube of [tex]\(-4\)[/tex]:
[tex]\[ (-4)^3 = -64 \][/tex]
Substitute [tex]\( -64 \)[/tex] back into the function:
[tex]\[ g(-4) = -2(-64) - 3 \][/tex]
Multiply the constants:
[tex]\[ -2 \cdot -64 = 128 \][/tex]
Finally, combine the terms:
[tex]\[ g(-4) = 128 - 3 \][/tex]
[tex]\[ g(-4) = 125 \][/tex]
So, [tex]\( g(-4) = 125 \)[/tex].
### Final Answers
[tex]\[ f(3) = -8 \][/tex]
[tex]\[ g(-4) = 125 \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.